2020
DOI: 10.1007/s42452-020-2645-z
|View full text |Cite
|
Sign up to set email alerts
|

Precipitator concentration-dependent opto-structural properties of MgO nanoparticles fabricated using natural brine

Abstract: In this paper, MgO nanoparticles (MNPs) were synthesized using simple wet chemical precipitation technique from evaporative brine as Mg ions precursor. The effect of NaOH concentration on morpho-structural and optical properties of as-synthesized nanoparticles was studied. The obtained nanoparticles were characterized by X-ray Diffraction (XRD), transmission electron microscopy (TEM), field emission scanning electron microscope (FESEM), energy dispersive X-ray (EDS), fourier transform infrared spectroscopy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Further, with increasing Pb content, average crystallite size deduced from XRD varies as compare to particle size analyzed through FESEM. This reveals that polycrystalline nature of nanocrystals approaching toward nearly single crystalline nature [48,57].…”
Section: Methodsmentioning
confidence: 87%
“…Further, with increasing Pb content, average crystallite size deduced from XRD varies as compare to particle size analyzed through FESEM. This reveals that polycrystalline nature of nanocrystals approaching toward nearly single crystalline nature [48,57].…”
Section: Methodsmentioning
confidence: 87%
“…Similarly, the resistivity of ITO nanoparticles decreases continuously with the decrease in N In /N a . It has been reported that the concentration of precipitant has an influence on growth rate and formation rate of crystal [35]. Sufficient precipitant not only ensures the complete precipitation of metal ions but also makes the particle size of R3 more uniform than others, which is conducive to the decrease in resistivity.…”
Section: Variance Analysis Of Orthogonal Experiments Resultsmentioning
confidence: 99%
“…A comparison of the doping specimens demonstrates that all spectra have identical signals since they all comprise the same key framework part, the MgO-NPs structures [52,53] nearly slight variation in the band's intensity in 3450-1650 cm -1 . This can be attributed to -OH stretching frequency assigned due to the hydroxyl group present in the oxide [47,54].…”
Section: Ftir Spectroscopy For (Mg(1-x)pbxo)-nps Specimensmentioning
confidence: 97%